d(sinx-cosx)=(sinx+cosx)dx,(sinx-cosx)=t,∫(sinx+cosx)/(sinx-cosx)^3dx =∫dt/t=∫tdt/(t)=(1/2)∫d(t)/(t)=(-1/2)*1/t+c=-1/[2(sinx-cosx)]+c.
求∫(sinx+cosx)/(sinx-cosx)^3dx 不定积分!
1个回答
相关问题
-
(3cosx–sinx)/(cosx+sinx) dx 求不定积分
-
求不定积分∫(sinx/(sinx+cosx))dx
-
求∫cosx/(sinx+cosx)dx的不定积分
-
求不定积分dx/((sinx)^3*(cosx)^5)
-
求不定积分:∫(sinx+cosx)^2/((sinx-cosx)√(1+sin2x))dx
-
求不定积分(sinx*cosx)/(sinx+cosx)
-
(cosx)^5(sinx)^4dx求不定积分,
-
求不定积分(1-sinx)/(cosx)^2 dx
-
求不定积分∫sinx-xcosx/cosx+xsinx dx
-
求不定积分∫TANX/(3SINX^2+COSX^2)DX